Project Based Learning and Epistemological Development on Undergraduate Students - Bontempo e Silva, Luiza (2022)
This paper is part of a bigger research that aims to understand how professional education delivered through Project-Based Learning (PBL) affects self-authorship development on undergraduate students. This part of the project aims to evaluate self-authorship development of undergraduate students enrolled on PBL during four to five years. The method used was qualitative, transversal, with biographical-narrative approach. In deep interviews were the instrument for data construction. Nine students of different semesters voluntarily participate on the interviews. Data analysis were based on categories validated on previous research, using the software Atlas.ti as a tool. Results found that practical experience during professional education would exert different effects on students depending on their self-authorship position. In addition, found that PBL on its own is not sufficient to generate movement to more sophisticated self-authorship positions, but it can support incipient movement underway.